Disaster-related resiliency theory among older adults who survived Typhoon Haiyan. (April 2019) - Almazan, Joseph U.; Albougami, Abdulrhman Saad; Alamri, Majed Sulaiman; Colet, Paolo C.; Adolfo, Cris S.; Allen, Kelly; Gravoso, Rotacio; Boyle, Christopher
Abstract: This study aims to describe and explain disaster-related resiliency from the perspective of older adult survivors through the grounded theory approach. A total of 14 older adults who survived Typhoon Haiyan participated in the study. These participants were chosen through purposive sampling, followed by theoretical sampling, to attain conceptual and theoretical saturation. Data were gathered through in-depth interviews, which took place in temporary shelter homes. Grounded disaster-related resiliency theory was generated on the basis of the subcategories and categories that were developed. The post-disaster recovery path can be conceptualized into three categories: (1) participants' perception of strength, (2) self-regulating behavior, and (3) maintaining a positive attitude. These categories provide coping mechanisms that are important in building resiliency following a natural disaster. The results of this study may provide a theoretical framework for the design and implementation of disaster risk protection strategies and policies for local governments at the international level. Highlights: A theory illustrates between older adult disaster experience and resilience. Older adults' perception and positivism enhance disaster resiliency. Self-regulating behaviors plays a critical role in disaster recovery. Results provide a theoretical framework to design a disaster risk protection strategy.